The Peroxiredoxin Repair Proteins - Jönsson, Thomas J. (2007)
Sulfiredoxin and sestrin are cysteine sulfinic acid reductases that selectively reduce or repair the hyperoxidized forms of typical 2-Cys peroxiredoxins within eukaryotes. As such these enzymes play key roles in the modulation of peroxide-mediated cell signaling and cellular defense mechanisms. The unique structure of sulfiredoxin facilitates access to the peroxiredoxin active site and novel sulfur chemistry.